A conceptual framework of the way forward to a community pharmacist–general practitioner collaborative medication therapy management model for chronic diseases in Malaysian primary care: a qualitative study - Mubarak, Naeem; Raja, Sarwat Ali; Sarwar Khan, Asma; Kanwal, Sabba; Saif-ur-Rehman, Nasira; Aziz, Muhammad Majid; Hussain, Irshad; Hatah, Ernieda; Zin, Che Suraya (Dove Medical Press, 2021)
Background: There is a growing global interest in formulating such policies and strategic plans that help devise collaborative working models for community pharmacists (CPs) and general practitioners (GPs) in primary care settings. Objective: To conceptualize a stakeholder-driven framework to improve collaboration between CPs and GPs in Malaysian primary care to effectively manage medicines in chronic diseases. Design and Setting: A qualitative study that involved individual semi-structured inter- views of the leadership of various associations, guilds, and societies representing CPs, GPs, and Nurses in Malaysia. Methods: This study collected and reported data in accordance with the guidelines of the Consolidated Criteria for Reporting of Qualitative Studies. Key informants were recruited based on purposive (expert) sampling. Interviews were transcribed verbatim and data were coded based on the principles of thematic analysis in NVivo. Results: A total of 12 interviews (5 CPs, 5 GPs, and 2 nurses) were conducted. Five themes emerged: Theme 1 highlighted a comparison of community pharmacy practice in Malaysia and developed countries; Theme 2 involved current practices in Malaysian primary care; Theme 3 encompassed the advantages of CP–GP collaboration in chronic diseases; Theme 4 highlighted the barriers which impede collaboration in Malaysian primary care; and Theme 5 delineated the way forward for CP–GP collaboration in Malaysia. Conclusion: The actionable insights obtained from the Malaysian stakeholders offered an outline of a framework to enhance collaboration between CPs and GPs in primary care. Generally, stakeholders were interested in CP–GP collaboration in primary care and identified many positive roles performed by CPs, including prescription review, adher- ence support, and patient education. The framework of the way forward includes: separation of CP and GP roles through a holistic revision of relevant legislation to grant an active role to CPs in chronic care; definition of protocols for collaborative practices; incentivization of both stakeholders (CPs and GPs); and design and implemen- tation of an effective regulatory mechanism whereby the Malaysian Ministry of Health may take a leading role